Guidelines for Conservation of the Built Heritage : Repair and maintenance of heritage structures on the inland waterways of Ireland.: Repair and maintenance of heritage structures on the inland waterways of Ireland. ([2016]) - Kelly, David, 1941-; O'Shaughnessy, Aighleann; Quinlan, Margaret
No abstract available